Topological structure effects of Laguerre-Gaussian laser on self-collimation acceleration mechanism - Dong, H.; Wang, W. P.; Lv, Z. X.; Jiang, C.; He, J. Z.; Leng, Y. X.; Li, R. X.; Xu, Z. Z. (Frontiers in Physics, 2022)
Energetic plasma beams can be generated through the interaction between a short-pulse high-intensity laser and solid target. However, obtaining collimated plasma beams with low di-vergence remains challenging. In this study, we devised a self-collimation scheme driven by a topologically structured Laguerre–Gaussian (LG) laser that irradiates a thin target in three-dimensional particle-in-cell simulations. It was observed that a high-density and narrow plasma beam could be formed by the intrinsic hollow intensity distribution of the LG laser. A magnetic tunnel was generated around the beam and collimated the plasma beam within a radius of hundreds of nanometers. This collimation can be enhanced by increasing the topological charge from l = 1 to l = 3 and then destroyed for a larger l. The collimation method is promising in ap-plications requiring well-collimated energetic plasma beams, such as indirect drive inertial con-finement fusion, laboratory astrophysics, and radiation therapy.